Relaciones interpersonales del clero secular jerezano a finales de la Edad Media - Ruiz-Berdejo-Beato, Alberto (2024)
This paper analyzes the interpersonal relationships established by the secular clergy in Jerez de la Frontera during the Late Middle Ages. Through the analysis of the affidavits preserved in the Historical Archive of Affidavits of Jerez de la Frontera for the period between 1392 and 1520, the most mundane profile of this important ecclesiastical group is traced. In this way, the article intends to go beyond the usual business in notarial documentation to delve into other types of connections, less obvious, but equally common between clergy and laity. It talks about their spiritual, material, social and sexual links, which give meaning to the adjective «secular» and show the social prestige enjoyed by this group in the society of this time.
Keywords: Baja Edad Media; Jerez de la Frontera; Reino de Sevilla; clero secular; protocolos notariales; relaciones carnales; relaciones espirituales; relaciones materiales; relaciones sociales